The Role of Sustainable Finance and Technology at Bank BJB in Supporting the "Sustainable Development Goals" - Franky Mogi Wuaten (Aptisi Transactions On Technopreneurship (ATT), 2023)
On September 25, 2015, UN member states raised a series of the 2030 Sustainable Development agenda which includes 17 Sustainable Development Goals (SDGs). The SDGs consist of: No poverty, No hunger, Healthy and prosperous life, Quality education, Gender equality, Clean water and proper sanitation, Clean and affordable energy, Decent work and economic growth, Industry-innovation and infrastructure, Less gap, Sustainable cities and settlements, Responsible consumption and production, Handling climate change, Marine Ecosystem, Land ecosystem, Peace-justice and strong institutions, Partnership to achieve goals. Fintech activities in small and medium enterprises in the community have been proven to be accelerated quickly with the digitization of MSMEs. This is supported by the availability of quality and sustainable infrastructure, as well as access to Information and Communication Technology (ICT).  The Government's commitment to implementing sustainable development is specifically regulated in the National Medium-Term Development Plan (RPJMN) for 2020-2024. Sustainable development has been defined as one of the important aspects that aim to provide access to equitable and inclusive development, as well as protect the environment. The role of sustainable finance in World Wildlife Funding ( WWF) and the Financial Services Authority (OJK) jointly encourage the Banking Industry to play a role in Sustainable Finance Development while supporting the process of community economic development. The activities above also make environmentalists, companies and the government mutually encourage all these positive activities to be carried out nationally and globally so as to contribute to sustainable economic development and support equality in the economic, social and cultural sectors.